Seismic response of random rubble stone masonry buildings from mid-hills of central Nepal - Adhikari, Rabindra; Shrestha, Ayush Raj; Aryal, Anu; Sharma, Binaya; Budhathoki, Abhishek; Bhatt, Bhawana; Bhandari, Biplov (Journal of Engineering Issues and Solutions, 2024)
Rubble stone masonry in mud mortar is the most prevalent stone masonry buildings in the mid-hills accounting for more than 70% of Nepali building stock. However, these types of construction are relatively more vulnerable to seismic events. Interestingly, some of these masonry buildings performed very well while many others collapsed. For a detailed understanding of performance of these masonry at component level during earthquake excitation, this paper presents the gradual failure mechanism for a typical stone masonry from mid-hills of central Nepal. The analysis was carried out by first linear analysis of Finite Element macro-model, followed by non-linear pushover analysis using finite element method and equivalent frame method. Performance was assessed under different levels of earthquake. Linear analysis results showed that these masonry buildings satisfy the drift requirements as per Nepal building code with adequate margin but are susceptible to heavy damages, especially in shear along with significant compression crushing and tensile cracks, under design level earthquake. Detailed non-linear analysis showed that the building attains performance states of immediate occupancy, life-safety, and collapse prevention at peak ground intensities of 0.175 g, 0.25 g and 0.295 g, respectively, while the analysis using equivalent frame model showed the performance at peak ground acceleration intensities of 0.15 g, 0.19 g and 0.3 g, respectively. The existing damage in the building with partial collapse of gable due to 2015 Gorkha earthquake with estimated exposed ground intensity of 0.18 g is well predicted by the analysis.